The influence of family social support on quality of life of informal caregivers of cancer patients - Margarita García‐Carmona; Francisco García‐Torres; Marcin Jacek Jabłoński; Ángel Gómez Solís; María José Jaén‐Moreno; Juan A. Moriana; María José Moreno‐Díaz; Enrique Aranda (Wiley, 2021)
Abstract Aim Caregivers of cancer patients are at high risk of experiencing impairments in terms of anxiety, depression and quality of life. This study examines the mediation capacity that perceived emotional support can have after diagnosis and six months later between depression and anxiety after diagnosis and quality of life in informal caregivers of cancer patients. Design A sample of 67 informal caregivers of cancer patients was used. This study is longitudinal, ex post facto prospective, with convenience sampling. Methods Participants completed the Medical Outcomes Study 36‐Item Short Form (SF‐36), the Hospital Anxiety and Depression Scale (HADS) and the Berlin Social Support Scale (BSSS) and a sociodemographic questionnaire. Data were collected between March 2017 and November 2018. Results Spearman's correlation analysis showed that anxiety, depression and perceived emotional support were related to quality of life. The mediation analysis showed that the relationship between depression after diagnosis and quality of life six months later was mediated by perceived emotional support.